The human sciences after the decade of the brain - Leefmann, Jon; Hildt, Elisabeth (Academic Press, 2017)
This book brings together new works that address today's key challenges for a mutual interaction between cognitive neuroscience and the social sciences and humanities. It addresses the methodological and conceptual problems of choosing a neuroscience approach to disciplines such as philosophy, history, ethics and education and examines a range of epistemological, historical, and sociological questions about the "neuro-turn" in the new millennium